2021
DOI: 10.1039/d1nr00169h
|View full text |Cite
|
Sign up to set email alerts
|

Self-supported nickel-doped molybdenum carbide nanoflower clusters on carbon fiber paper for an efficient hydrogen evolution reaction

Abstract: Developing an efficient, stable and low-cost noble-metal-free electrocatalyst for the hydrogen evolution reaction (HER) is an effective way to alleviate the energy crisis. Herein, we report a simple and facile...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 74 publications
3
42
0
Order By: Relevance
“…Following previous reports on cyclic divalent species, [20][21][22][23][24][25][26][27][28] organic compounds and nanostructures, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] now we compare and contrast new rNHGes (1-10) by fusion of one benzene, pyrrole, phosphole, furan and thiophene ring in "orthoor zigzag" arrangement and "paraor chair" arrangement to 1H-4-germapyridine-4-ylidene (1) as the reference germylene.…”
Section: Methodsmentioning
confidence: 89%
“…Following previous reports on cyclic divalent species, [20][21][22][23][24][25][26][27][28] organic compounds and nanostructures, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] now we compare and contrast new rNHGes (1-10) by fusion of one benzene, pyrrole, phosphole, furan and thiophene ring in "orthoor zigzag" arrangement and "paraor chair" arrangement to 1H-4-germapyridine-4-ylidene (1) as the reference germylene.…”
Section: Methodsmentioning
confidence: 89%
“…As a starting material for the preparation of molybdenum carbide using molten salt synthesis, MoO 3 has been used. Hu et al [150] described the method of preparation of molybdenum carbide doped with nickel supported on carbon fiber paper (CFP). For synthesis, CFP was impregnated with nickel ions.…”
Section: Molten Salt Synthesismentioning
confidence: 99%
“…Since the active β ‐phase Mo 2 C has been initially discovered in 2012, the research of Mo 2 C was increased rapidly although it‘s activity was not yet preeminent enough to unseat Pt‐based catalyst [12] . Further studies indicated that the excessively powerful Mo−H binding energy hindered the desorption of H ads to form hydrogen, which was the main factor effecting the catalytic performance of Mo 2 C. By doping the electron‐rich transition metals (such as Fe, Co, Ni and other elements in VIII group) to decrease the occupied d orbital of Mo, or building abundant defects on the surface can transform the surface charge density distribution of the catalyst, so as to optimize the intensity of the Mo−H bond, and then promote the electrocatalytic activity of Mo 2 C [13–19] . For example, Gao et al.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Since the active β-phase Mo 2 C has been initially discovered in 2012, the research of Mo 2 C was increased rapidly although it's activity was not yet preeminent enough to unseat Pt-based catalyst. [12] Further studies indicated that the excessively powerful MoÀ H binding energy hindered the desorption of H ads to form hydrogen, which was the main factor effecting the catalytic performance of Mo 2 C. By doping the electron-rich transition metals (such as Fe, Co, Ni and other elements in VIII group) to decrease the occupied d orbital of Mo, or building abundant defects on the surface can transform the surface charge density distribution of the catalyst, so as to optimize the intensity of the MoÀ H bond, and then promote the electrocatalytic activity of Mo 2 C. [13][14][15][16][17][18][19] For example, Gao et al successfully doped Co in Mo 2 C nanowires, which significantly increased the electron density around the Fermi level in Mo 2 C and weakened the adverse effect of MoÀ H on HER kinetics, rendering the prepared Co-Mo 2 C was able to reach 10 mA cm À 2 at 140 mV. [20] Li and her co-worker employed SiO 2 as a hard template to synthesize β-Mo 2 C nanoparticles with rich Mo vacancies by dangerous hydrofluoric acid (HF) etching, which showed excellent HER activity.…”
Section: Introductionmentioning
confidence: 99%